Myocardial Infarction Thought to be Provoked by Local Epinephrine Injection During Endoscopic Submucosal Dissection - Kim, Hyung Hun (Elmer Press, 2011)
Due to its hemostatic effect, local epinephrine has been used to minimize mucosal bleeding during endoscopic submucosal dissection (ESD), but its clinical benefit remains unclear. On the other hand, several adverse events deemed to be caused by epinephrine have been observed during ESD. A 73-year-old woman developed myocardial infarction after ESD for a large rectal adenoma, and an 80-year-old woman developed abrupt chest tightness during ESD. In both patients, changes on electrocardiogram and elevated cardiac markers provided evidence of myocardial ischemia. The patients were transferred to the cardiac care unit and recovered completely. Up to our knowledge this is the first report of myocardial infarction thought to be provoked by submucosal epinephrine injection during ESD. KEYWORDS: Adenoma; Colon; Endoscopic surgical procedure; Epinephrine; Myocardial infarction